Al-driven peculiarities of local coordination and magnetic properties in single-phase Al x-CrFeCoNi high-entropy alloys - Smekhova, Alevtina; Kuzmin, Alexei; Siemensmeyer, Konrad; Luo, Chen; Chen, Kai; Radu, Florin; Weschke, Eugen; Reinholz, Uwe; Buzanich, Ana Guilherme; Yusenko, Kirill V. (Tsinghua University Press, 2021)
Modern design of superior multi-functional alloys composed of several principal components requires in-depth studies of their local structure for developing desired macroscopic properties. Herein, peculiarities of atomic arrangements on the local scale and electronic states of constituent elements in the single-phase face-centered cubic (fcc)- and body-centered cubic (bcc)-structured high-entropy Alx-CrFeCoNi alloys (x = 0.3 and 3, respectively) are explored by element-specific X-ray absorption spectroscopy in hard and soft X-ray energy ranges. Simulations based on the reverse Monte Carlo approach allow to perform a simultaneous fit of extended X-ray absorption fine structure spectra recorded at K absorption edges of each 3d constituent and to reconstruct the local environment within the first coordination shells of absorbers with high precision. The revealed unimodal and bimodal distributions of all five elements are in agreement with structure-dependent magnetic properties of studied alloys probed by magnetometry. A degree of surface atoms oxidation uncovered by soft X-rays suggests different kinetics of oxide formation for each type of constituents and has to be taken into account. X-ray magnetic circular dichroism technique employed at L2.3 absorption edges of transition metals demonstrates reduced magnetic moments of 3d metal constituents in the sub-surface region of in situ cleaned fcc-structured Al0.3-CrFeCoNi compared to their bulk values. Extended to nanostructured versions of multicomponent alloys, such studies would bring new insights related to effects of high entropy mixing on low dimensions. [Figure not available: see fulltext.] © 2021, The Author(s). --//-- This is the accepted version of the article: Smekhova, A., Kuzmin, A., Siemensmeyer, K. et al. Al-driven peculiarities of local coordination and magnetic properties in single-phase Alx-CrFeCoNi high-entropy alloys. Nano Res. (2021). https://doi.org/10.1007/s12274-021-3704-5. Accepted manuscript's terms of use: https://www.springernature.com/gp/open-research/policies/accepted-manuscript-terms
The authors thank the Helmholtz-Zentrum Berlin for the provision of access to synchrotron radiation facilities and allocation of synchrotron radiation at the PM2-VEKMAG, BAMline, and UE46_PGM-1 beamlines of BESSY II at HZB as well as measurement time for magnetometry at HZB CoreLab for Quantum Materials. A. S. acknowledges personal funding from CALIPSOplus project (the Grant Agreement no. 730872 from the EU Framework Programme for Research and Innovation HORIZON 2020). The financial support for the VEKMAG project and the PM2-VEKMAG beamline by the German Federal Ministry for Education and Research (Nos. BMBF 05K10PC2, 05K10WR1, 05K10KE1) and by HZB is cordially acknowledged by all co-authors. Steffen Rudorff is acknowledged for technical support. Institute of Solid State Physics, University of Latvia as the Center of Excellence has received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES; element-specific spectroscopy; extended X-ray absorption fine structure (EXAFS); high-entropy alloys; magnetism; reverse Monte Carlo; X-ray magnetic circular dichroism (XMCD)